Investigating the “off-hour effect” on outcomes of neonates undergoing emergency gastrointestinal surgery - Yu Cui (PeerJ)
Background Evidence regarding the off-hour effect on outcomes in neonates with gastrointestinal disease who received urgent surgical intervention is unknown. Because of the workforce shortage, insufficient experience of surgeons, and delayed radiography examination during off-hours, we hypothesized that emergency surgeries performed during off-hours were associated with worse outcomes. This study aims to analyze the association between the “off-hour effect” and adverse events of neonates undergoing emergency gastrointestinal surgery. Methods We extracted patient data from the electronic medical record system at our institution for all neonates undergoing emergency gastrointestinal surgery between July 2018 and October 2021. The primary outcomes were 24-hour and in-hospital mortality. The secondary outcomes were actual postoperative length of stay (PLOS) and the incidence of unplanned re-operation. Results A total of 275 neonates were identified, and 207 (75.3%) were treated during off-hours. The “off-hour effect” was not associated with increased 24-hour mortality, in-hospital mortality, PLOS, and unplanned re-operation. After propensity score matching, 68 off-hours were matched to the nearest 68 on-hours based on their age, weight, gestation weeks, and American Society of Anesthesiologists (ASA) status. No differences were detected in the primary and secondary outcomes. Conclusion In this retrospective study with neonates who underwent emergency gastrointestinal surgery, after controlling for age, weight, gestation weeks, and ASA status, surgical and medical outcomes were not different in those undergoing off-hours surgery, which can be considered a surrogate for similar quality of care. However, in the future, a multi-center, prospective study is needed to confirm the results, to overcome the bias related to the presence of only one surgical team.